Structural and dielectric properties of Zr doped BaTiO3 synthesized by microwave assisted chemical route - Al-Hilli, Muthafar F. Jamil (Iraqi Journal of Science, 2018)
Lead-free ferroelectric nano ceramics of BaZrxTi1-xO3 (x=0.1, 0.2 and 0.3) were prepared by means of microwave assisted chemical route. The structural, dielectric and electrical properties were examined. The crystalline structure of the specimens was studied by X-ray diffraction patterns. All the samples showed pure single phase of perovskite structure with space group of I4/mcm. X-ray diffraction data illustrated that there is no secondary phases exist. Structural and electrical properties of barium titanate ceramics are influenced significantly by small additions of Zr. The electrical conductivity showed higher values at x=0.2 and decreased at higher Zr content. The Hall charge mobility is found to decrease with Zr addition. The negative sign of theHall coefficient RH confirms the dominant n-type conduction in all samples. The charge carrier concentration decreased with Zr content increase. Suggested potential application for this ceramics compound is in high storage multilayer capacitors and ferroelectric applications.